Final cut pro X beyond the basics : advanced techniques for editors - Wolsky, Tom (Routledge, Taylor & Francis Group, 2018)
"Going beyond where introductory books leave off and written for experienced editors, especially those new to Final Cut Pro X, this new and revised edition of Final Cut Pro X Beyond the Basics is brimming with cutting-edge methods to bring your editing skills to the next level. Explained in jargon-free language by a seasoned teacher and digital editor, Tom Wolsky's text has been fully updated to address the new Final Cut Pro X 10.3 interface and changes to the software. This full-color workshop features tutorials that provide firsthand experience on the art and technique of editing at an advanced level with Final Cut Pro X, as well as in-depth information and time-saving tips that will allow you to master the application's interface elements, tools, and nuances. Wolsky covers all the bases, including:Library workflows and collaboration;Media organization and metadata customization for different genres;Editing techniques for projects of various lengths and types;Using markers and the timeline index;Audio tools;Multicam editing;Audio and video effects;Color correction, including secondary corrections and isolated color adjustments;Compositing and complex animation. An accompanying eResource features downloadable Final Cut Pro X project libraries for the tutorials discussed in the book, offering readers hands-on examples of the techniques and practices covered."--Provided by publisher.